Pengaruh Price dan Location terhadap Customer Loyalty Melalui Customer Satisfaction pada Aone Trawas - Muhammad Luthfi Alif Utama; Fitri Dhea Lusanti; Putri Dhea Lusanti (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze and evaluate the impact of price and location on customer loyalty, with customer satisfaction acting as a mediating variable. The research employs a quantitative approach, utilizing probability sampling with a random sampling technique, involving 100 respondents who are customers of AONE Trawas. Data analysis was conducted using SmartPLS software version 3.0. The results of hypothesis testing indicate that location significantly affects both customer loyalty and customer satisfaction, as evidenced by T-statistic values exceeding 1.96 and p-values below 0.05. Furthermore, location contributes meaningfully to enhancing customer loyalty through the mediation of customer satisfaction. This finding suggests that customer satisfaction plays a crucial role in strengthening the link between location and loyalty. In contrast, the price variable does not show a significant influence, either directly on customer loyalty and satisfaction or indirectly through the mediation of customer satisfaction. This is supported by T-statistic values below 1.96 and p-values above 0.05 for all relationships involving the price variable. These results highlight the importance of location in driving customer loyalty.